Reconstruction Using Free Flaps for Diabetic Heel Defects: Outcomes and Risk Factor Analysis - Kim, Hyung Bae; Altiparmak, Mehmet; Pak, Changsik John; Suh, Hyunsuk Peter; Hong, Joon Pio (Journal of Reconstructive Microsurgery, 2020)
Background Overall success rate after diabetic foot reconstruction using free flap has been acceptable, but certain parts of the foot like the heel remains more challenging.Patients and Methods This retrospective study reviewed 37 patients reconstructed with free flaps for diabetic foot ulcer on the heel region from 2008 to 2017. Flap outcome in addition to various risk factors were analyzed; arterial status on heel, the American Society of Anesthesiologists (ASA) physical status, smoking, hypertension, hypercholesterolemia, chronic renal failure patient, hemoglobin A1c level, C-reactive protein, and osteomyelitis.Results Overall flap survival was 73% and resulted in limb salvage and functional ambulation. Total flap loss was 27% and the majority ended up with high-level amputation. Among the risk factors evaluated, the arterial status of the heel and ASA status significantly increased the odds for failure. When both arterial branches to the heel were impaired, the odds of failure were 80 times higher to fail (p< 0.05).Conclusion The vascularity of the surrounding tissue of the defect plays a critical role in overall success of diabetic heel reconstruction. Aggressive debridement using the angiosome concept is necessary to assure surrounding tissue has a good circulation. Despite the high chance of failure, success will lead to limb salvage and to reasonable functional ambulation whereas failure to salvage the heel will lead to higher level amputation. This warrants microsurgeons to make an effort to perform reconstruction to the heel defect after obtaining maximal vascularity after angioplasty.
Keywords: diabetic foot reconstruction; microsurgery; free flaps